Analisis Penilaian Tingkat Kesehatan Bank dengan Metode RGEC Pada PT Bank BRI Syariah (Persero) 2013-2018 - Hadi Samanto; Nurul Hidayah (ITB AAS INDONESIA Surakarta, 2020)
The purpose of this research is to determine the influence of the four aspects of RGEC on the assessment of the bank's health level at PT Bank Rakyat Indonesia Syariah. This research uses RGEC method consisting of risk profile, good corporate governace, earning and capital. The sampling techniques in this study used saturated sample methods. And the sample used in this study is the financial statements of PT. Bank BRI Syariah from 2013 to 2018. As one of the sharia public banks in Indonesia, BRI Syariah Tbk bank must maintain the bank's health level in the following years in order to maintain public trust, customers and stake holders towards BRI Syariah Tbk bank. There are several assessment indicators in certain years that fluctuate, this needs to be considered so that in the following years the indicator is maintained stability so as not to adversely affect performance. PT Bank BRI Syariah Tbk also needs to lower operating costs from rank 5 which is unhealthy to rank 1 very healthy in order to maintain the company's performance by increasing profit, especially operating profit. PT Bank BRI Syariah Tbk also needs to lower the percentage rate of Earnings (Rentability) from unhealthy, unhealthy, healthy enough to be a healthy or very healthy rating, with the aim of ordering PT. Bank BRI Syariah Tbk has a higher profit.